Dominance of Fagus sylvatica in the Growing Stock and Its Relationship to Climate—An Analysis Using Modeled Stand-Level Climate Data - Nina Škrk; Roberto Serrano-Notivoli; Martín de Luis; Katarina Čufar (Plants, 2022)
In the future, climate change is expected to affect the spatial distribution of most tree species in Europe. The European beech (Fagus sylvatica), a drought-sensitive tree species, is currently distributed throughout Europe, where it is an ecologically and economically important species. In Slovenia, the European beech represents 33% of the growing stock, but such a proportion greatly varies across Europe. Whether such a variation is related to the climate environmental gradients or because of historical or management decisions is an as-yet unexplored question. For this study, we employed the Slovenian Forests Service inventory, where the proportion of beech in the forest stock has been monitored in 341,341 forest stands across the country. Modeled climate data from the SLOCLIM database, calculated for each of the stands, was also used to test the hypothesis that although beech forests have always been influenced by human activity, the dominance of beech trees in forest stands is at least partially dictated by the climate. The results showed the distribution of the main climate variables (annual precipitation, the share of summer and spring precipitation, and annual maximum and minimum temperatures) and how they affect the current dominance of beech trees at the stand level. Due to the large number and variability of forest stands studied, the results should be transferable to better understand and manage the climatic suitability and risks of Fagus sylvatica. The modeled data is publicly available in the web repository Zenodo.